Community Preferences Determine Shape and Appearance of Residential Buildings in Compliance with Perwali No 25 Year 2010 in Denpasar Selatan - Putra, Kadek Wigunantara Eka; Muktiwibowo, Antonius Karel; Rajendra, I Gusti Ngurah Anom (Journal of A Sustainable Global South; Vol 5 No 1 (2021): February 2021DO - 10.24843/jsgs.2021.v05.i01.p05, 2021)
This study aims to determine the level of community compliance in South Denpasar and differences in people's preferences in complying with Mayor Regulation No. 25/2010. The research method used in this research is descriptive quantitative method with a survey approach. The number of respondents in the study were 100 people who were selected using multy stage sampling. The analysis technique used is the Frequency Distribution Analysis Technique (New Rank) and the Analytical Hierarchy Process (AHP). While the validity test was carried out by using the Product Moment Correlation Technique and the reliability test with Cronbach's Alpha. Public preferences in complying with Mayor Regulation No. 25/2010 vary widely, because each community group has different desires with their respective priority values for research aspects, as well as the level of compliance obtained from field findings. Communities with higher income have a higher level of compliance than others, but do not have a good scale of attitude towards compliance with applicable regulations, and vice versa. Index Terms — preference, compliance, regulation.